PEMEROLEHAN KLAUSA RELATIF PADA PEMELAJAR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA): KAJIAN BAHASA-ANTARA - Suharsono Suharsono (LITERA, 2015)
AbstractThis study aims to describe the acquisition of relative clauses by BIPA (Bahasa Indonesiafor Foreigners) learners of the intermediate level, in terms of: (a) relative clause forms, (b)the sequence of relative clause acquisition, and (c) effects of language learning strategieson the relative clause acquisition. The data were collected from the use of Indonesian byBIPA learners attending a language program and through a questionnaire. The languagedata were analyzed by the translational equivalence and distributional methods and thequestionnaire data by the calculation of means and percentages presented in tables andgraphs. The results of the study showed that the use of the relative pronoun yang wasthe item with the lowest acquisition level and the relative clause type relativizing thesubject was in the highest rank. Meanwhile, the use of language learning strategies hada positive correlation with the relative clause acquisition. The study concludes that: (1)the sequence of the relative clause acquisition reflects both the sequence of mastery andthe difficulty level of of each clause type, and (2) the use of language learning strategiesenables learners to acquire relative clauses faster.